2023
DOI: 10.2991/978-94-6463-268-2_29
|View full text |Cite
|
Sign up to set email alerts
|

National Independent Innovation Demonstration Zone, Industry Agglomeration and Regional Innovation Capability-Research based on high-tech service industry

Lingjing Wang,
Yilin Ding,
Yunchang Tian

Abstract: Under the background of accelerating scientific and technological progress and continuous expansion of technology scale in China, the policy of national independent innovation demonstration zones has been continuously deepened and improved, which promotes the development, transformation and upgrading of innovative economy in China and provides important support for the construction of regional innovation system. Based on the panel data of 285 cities in China from 2003 to 2020, this paper uses the difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…At the same time, it is negatively affected by the overall spatial spillover effects of diversified agglomeration. Wang et al (2022), from the external perspective of industrial agglomeration, examined the impact of high-tech industrial agglomeration on regional innovation capability based on 30 Chinese provinces. The research results indicated that both specialized and diversified agglomeration patterns in high-tech industries significantly enhance regional innovation capability.…”
Section: Impact Of Industrial Agglomeration On Regional Innovationmentioning
confidence: 99%
“…At the same time, it is negatively affected by the overall spatial spillover effects of diversified agglomeration. Wang et al (2022), from the external perspective of industrial agglomeration, examined the impact of high-tech industrial agglomeration on regional innovation capability based on 30 Chinese provinces. The research results indicated that both specialized and diversified agglomeration patterns in high-tech industries significantly enhance regional innovation capability.…”
Section: Impact Of Industrial Agglomeration On Regional Innovationmentioning
confidence: 99%